Field efficacy of white muscardine fungus (Beauveria bassiana) on rice hispa (Dicladispa armigera) - HAZARIKA, L K; PUZARI, K C (The Indian Journal of Agricultural Sciences, 2013)
A field trial was conducted for 4 years (1989-93) in different rice (Oryza sativa L.) seasons at various areas endemic to rice hispa [Dicladispa armigera (Olivier)] (Coleoptera: Chrysomelidae) in Assam to assess the efficacy of a mycopathogen, Beauveria bassiana (Bals.) vuill. for controlling the insect. Multi-loeational fIeld trials with B. bassiana (10 million spores/ml dilution), 1 % neem-seed oil and a conventional insecticide (0.072% monocrotophos) revealed that the mycoparasite was superior to neem-seed oil but at par with monocrotophos in controlling the rice hispa, leading to increase in yield.